Evaluating heavy metal contamination and ecological risks in rivers surrounding Banyuroto Landfill in Indonesia - Iresha, Fajri Mulya; Asri, Tegar Kusuma; Kasam, Kasam (Applied Research in Science and Technology, 2023)
This study, carried out between May and June 2023, aimed to assess the influence of landfill leachate on environmental conditions, specifically regarding the pollution of river water near the Banyuroto landfill. The parameter of the difference heavy metals in this study are Mercury (Hg), Cadmium (Cd), Lead (Pb), Chromium (Cr), Manganese (Mn), Copper (Cu), and Iron (Fe). The potential ecological risk index is investigated due to the harm to the nearby river ecology. The sampling was conducted at eight discrete locations in close proximity to the dump. The levels of heavy metals were quantified using Atomic Absorption Spectroscopy (AAS). Furthermore, the Potential Ecological Risk (PER) technique was utilized to assess the potential environmental dangers that these metals may pose. The findings unveiled disparate concentrations of heavy metals across the various locations where point 5 of the sampling become most polluted area due to increased anthropogenic activities. The Mercury (Hg) concentrations ranged from 0.014 to 0.032 mg/kg, whereas the Cadmium (Cd) and Chromium (Cr) levels exhibited minimal variation in the below Limit of Detection (LOD). Lead (Pb) exhibited LOD readings, suggesting their minimum presence. The concentrations of Manganese (Mn) and Copper (Cu) were relatively low, whereas Iron (Fe) exhibited the greatest levels, ranging from 0.2405 to 1.2209 mg/l. The maximum potential ecological risk values were calculated and ranked from highest to lowest as follows: Hg (262.19) > Fe (20.35) > Cr (0.374) > Cd (0.245) > Cu (0.297) > Mn (0.100). Remarkably, the possible environmental hazards associated with all heavy metal characteristics constantly remained below the threshold of 40 except the maximum concentration of the total of Heavy Metals. This indicates that their concentrations present a substantial ecological danger in some situations.